Screening of West Nile Virus, Herpesvirus, and Parvovirus in Rattus spp. in Klang Valley, Malaysia - Natasha, Jafar Ali; Yasmin, Abd Rahaman; Siti-Maisarah, Abd Manan; Nur-Anis, Zakaria; Tharshaini, Murugasu; Arshad, Siti Suri; Ayuni, Wan Noor; Mohammed, Mohammed Nma; Nur-Fazila, Saulol Hamid (Universiti Putra Malaysia Press, 2022)
Free-roaming and scavenging lifestyles of Rattus spp. in densely populated urban areas expose them to multiple pathogens that facilitate the transmission of infection to the human population more rapidly, raising public health concerns. There is limited information on the status of rat susceptibility to virus infection, particularly West Nile virus (WNV), herpesvirus, and parvovirus, to prepare for emerging zoonosis. A total of 23 (n = 23) blood samples collected from Rattus spp. in the wet market areas of Klang Valley, Malaysia, were subjected to molecular assay using a one-step reverse transcription-polymerase chain reaction (RTPCR) to detect the highly conserved region of the WNV capsid and pre-membrane protein via nested polymerase chain reaction (PCR) assay targeting highly conserved aminoacid motifs within the herpesviral DNAdirected DNA polymerase gene (DPOL)and polymerase chain reaction (PCR) assay targeting the parvovirus non-structural (NS) protein. As a result, 4 out of 23 (17.39%) rats were positive for herpesvirus DNA, but none were positive for WNV RNA and parvovirus DNA. The positive PCR amplicons of herpesvirus DNA were subjected to partial DNA sequencing analysis, 100% identical to Acomys herpesvirus SVMS 226,222 from Betaherpesvirinae, which is highly suggestive of rat cytomegalovirus (RCMV). This study has successfully demonstrated the presence of RCMV from Rattus spp. in the Klang Valley. The RCMV potentially crosses species barriers and establishes infection, raising public health concerns. The non-viraemic state of WNV or parvovirus infection, low sample size, and limited niche distribution emphasise the need for the expansion of this study in the future.